Directory of Jamaica Tertiary Institutions - The University Council of Jamaica (The University Council of Jamaica, 1992)
This directory provides general information on programmes available at 48 tertiary institutions in Jamaica. Chapter One introduces each institution, and provides information such as address, telephone number, admission requirements, enrolment and staffing. Chapter Two provides a listing of the programmes offered by each institution, including the duration of each programme and the award received on completion of the course of study. Chapter Three provides an alphabetical index of programmes/courses, and Chapter Four provides an alphabetical listing of the institutions.
Keywords: Higher education